Facile Preparation of Stereoblock PLA From Ring-Opening Polymerization of rac-Lactide by a Synergetic Binary Catalytic System Containing Ureas and Alkoxides - Kan, Ze; Luo, Wenlong; Shi, Tong; Wei, Chuanzhi; Han, Binghao; Zheng, Dejuan; Liu, Shaofeng (Frontiers in Chemistry, 2018)
Ring-opening polymerization (ROP) of cyclic esters/lactones by efficient catalysts is a powerful method for synthesis of biodegradable and biocompatible polyesters with well-defined structures. To develop catalytic systems that are fast, selective and controlled is a persistent effort of chemists. In this contribution, we report a binary urea/alkoxide catalytic system that could catalyze ROP of rac-LA in a fast (over 90% conversion within 1-2 minutes), stereoselective (Pi up to 0.93) and controlled manner, indicated by narrow MW distributions, linear relationship between the monomer conversions and Mns, end-group fidelity and chain extension experiments. Remarkably, the catalytic system described here is simple, easily prepared, and structurally tunable and thus has versatile catalytic performances.